2020
DOI: 10.1111/pde.14467
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent angioedema in childhood: hereditary angioedema or histaminergic angioedema?

Abstract: The exact rate of prevalence of pediatric angioedema is not well known, and any reported rate will change with the presence of urticaria, or due to a specific cause of angioedema. The lifetime prevalence of non-hereditary angioedema was shown to be 4.9%-7.4% in two large nationwide studies. 1,2 However, information about the prevalence of recurrent histaminergic angioedema (HA) and its clinical presentation in children is limited. Considering only patients with hereditary angioedema (HAE), it has been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…With regard to locations and symptoms, significant differences could not be identified consistent with published data 21,33,34,41,42 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…With regard to locations and symptoms, significant differences could not be identified consistent with published data 21,33,34,41,42 …”
Section: Discussionsupporting
confidence: 74%
“…Significantly increased Tie-2 and VE-Cadherin levels were characteristic for HAE compared to ACE-AE, CSU-AE, and controls (Figure 1E With regard to locations and symptoms, significant differences could not be identified consistent with published data. 21,33,34,41,42 In summary, no distinct diagnostic relationship was found, not even for BK-versus histamine-mediated angioedema, despite the finding that some clinical characteristics were more frequently associated with a certain angioedema type, there was no diagnostic clue, not even for BK-versus histamine-mediated angioedema. Regarding clinical characteristics at visit 1, our limited study has evaluated only past events and includes only small populations.…”
Section: Clinical and Routine Laboratory Characteristicsmentioning
confidence: 88%
“…To the best of our knowledge, only the prospective study (95 patients) by Ertoy Karagol et al and the retrospective study (42 patients) by Ocak et al deepen this theme in the pediatric age [9,38]. Specifically, these studies included subjects affected by histamine-mediated AEwW, including in their cohorts patients affected by AE with poor response to antihistamines, the simultaneous presence of urticaria, or positive family history of AE [9,38]. Cross-sectional studies on pediatric populations identified a prevalence of 1.6% of isolated AE [9].…”
Section: Pediatric Features Of Acquired or Idiopathic Histamine-media...mentioning
confidence: 99%
“…Little is known about the prevalence, clinical presentation, etiology, management, and follow-up of pediatric-acquired or idiopathic isolated histamine-mediated AE. To the best of our knowledge, only the prospective study (95 patients) by Ertoy Karagol et al and the retrospective study (42 patients) by Ocak et al deepen this theme in the pediatric age [9,38]. Specifically, these studies included subjects affected by histamine-mediated AEwW, including in their cohorts patients affected by AE with poor response to antihistamines, the simultaneous presence of urticaria, or positive family history of AE [9,38].…”
Section: Pediatric Features Of Acquired or Idiopathic Histamine-media...mentioning
confidence: 99%
“…In mast-cell-induced angioedema, IgE-mediated angioedema is closely associated with a histamine-mediated mechanism, which is a Type I allergic reaction to drugs and external allergens [13,14]. ACE inhibitor is the major representative trigger of non-IgE-mediated angioedema.…”
Section: Angioedema Pathogenesismentioning
confidence: 99%